Mengamankan Catatan Akademik dengan Teknologi Blockchain Pendekatan Berbasis Data untuk Manajemen Universitas - Vaher, Kristina; Simanjuntak, Arthur; Sugiharto, Erwin (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2025)
In the contemporary landscape of higher education, background the burgeoning volume of digital academic records necessitates robust security and integrity measures, particularly amidst increasing concerns over data breaches and authenticity. Traditional centralized database systems, while functional, often present vulnerabilities that compromise student data privacy and the verifiable nature of academic achievements, thereby hindering efficient data-driven management. Object this study aims to propose and analyze a blockchain-based framework for securing academic records, thereby enhancing data integrity, transparency, and trust within university management systems through a data-driven approach. Method employing a qualitative research methodology, this paper reviews existing literature on blockchain applications in education, analyzes current challenges in academic record management, and develops a conceptual model illustrating how distributed ledger technology can be integrated to create a more secure and immutable repository for student credentials and institutional data. Furthermore, we explore the potential impact on privacy preservation and the streamlining of administrative processes. Result our findings indicate that blockchain technology offers a promising solution to mitigate inherent risks in conventional record-keeping systems by providing an unalterable, transparent, and decentralized ledger. This integration significantly bolsters data authenticity, reduces fraudulent activities, and fosters greater trust among stakeholders, ultimately supporting more reliable and effective data-driven decision-making for university administration. Conclusion the implementation of a blockchain-enabled system for academic records is critical for establishing a secure, verifiable, and efficient data management ecosystem in higher education, paving the way for enhanced operational excellence and stakeholder confidence in the digital age.